Maritime chemical logistics: Importance of optimization modeling and research opportunities - Oh, H.-C. (2014)
10th Int. Workshop on Harbor, Maritime and Multimodal Logistics Modeling and Simulation, HMS 2008, Held at the International Mediterranean and Latin American Modeling Multiconference, I3M 2008